A photoelectrochemical reactor for ion separation and hydrogen production - Aydin, Muhammed Iberia; Selcuk, Huseyin; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Global water demand has been rising rapidly due to increased industrial activities and personal consumption. The regulations and restrictions specifically introduced to achieve sustainable environmental targets have pushed the industry to adopt effective treatment methods to reuse the wastewater streams accordingly. For this reason, developing such systems that can produce reusable and useful by-products is important along with wastewater treatment. Accordingly, a photoelectrochemical reactor is designed and studied for the treatment of textile wastewaters and reclamation of sodium hydroxide. The presently designed reactor combines some of the aspects of photoelectrochemical cells and electrodialysis process. Various potentials are considered and applied to the reactor to investigate the hydrogen production rates and efficiencies of the reactor. The conductivity removal efficiencies are then found to be 37%, 39%, 55%, 66%, 87% while the color removal efficiencies are 96%, 95%, 91%, 75%, 74% for 1.7, 1.9, 2.1, 2.3 and 2.5 V, respectively. Furthermore, the hydrogen production rates for illuminated studies are measured as 0.024, 0.041, 0.061, 0.170, 0.302 mmol/h, respectively. (c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Energy; Efficiency; Photoelectrochemical method; Hydrogen production; Ion removal; Wastewater treatment; DYE WASTE-WATER; PHOTOCATALYTIC DEGRADATION; TIO2 PHOTOCATALYSIS; RECOVERY; Thermodynamics; Energy & Fuels